Pitfalls in the measurement of muscle mass: a need for a reference standard. Issue 2 (19th January 2018) - Buckinx, Fanny; Landi, Francesco; Cesari, Matteo; Fielding, Roger A.; Visser, Marjolein; Engelke, Klaus; Maggi, Stefania; Dennison, Elaine; Al‐Daghri, Nasser M.; Allepaerts, Sophie; Bauer, Jurgen; Bautmans, Ivan; et al.
Abstract: Background: All proposed definitions of sarcopenia include the measurement of muscle mass, but the techniques and threshold values used vary. Indeed, the literature does not establish consensus on the best technique for measuring lean body mass. Thus, the objective measurement of sarcopenia is hampered by limitations intrinsic to assessment tools. The aim of this study was to review the methods to assess muscle mass and to reach consensus on the development of a reference standard. Methods: Literature reviews were performed by members of the European Society for Clinical and Economic Aspects of Osteoporosis and Osteoarthritis working group on frailty and sarcopenia. Face‐to‐face meetings were organized for the whole group to make amendments and discuss further recommendations. Results: A wide range of techniques can be used to assess muscle mass. Cost, availability, and ease of use can determine whether the techniques are better suited to clinical practice or are more useful for research. No one technique subserves all requirements but dual energy X‐ray absorptiometry could be considered as a reference standard (but not a gold standard) for measuring muscle lean body mass. Conclusions: Based on the feasibility, accuracy, safety, and low cost, dual energy X‐ray absorptiometry can be considered as the reference standard for measuring muscle mass.